2019
DOI: 10.6007/ijarbss/v8-i12/5259
|View full text |Cite
|
Sign up to set email alerts
|

“Social Corporation” The Sharia Business Entity Model: A Corporate Structure with Embodied CSR

Abstract: Corporate social responsibility has been widely and internationally accepted as an element of good governance and one of the key factors in sustainability of a business. Nonetheless, the inculcation and practices of CSR are still subjected to discretion of the companies. In the present corporate model, CSR is still an option to be practiced rather than part of the objective of the company. Under the Sharia, it is also important for the businessmen to undertake that the main purpose or object of carrying out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It may foster buyers' confidence that the firms have concern on the quality standards, enhance the corporate reputation and cares about the community and environmental welfares. Previous studies also confirmed that CSR practice is important as a sustainable strategy to growth and compete longer in the business (Desiyanti & Kassim, 2020;Ghadas et al, 2018;Samuel et al, 2011).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…It may foster buyers' confidence that the firms have concern on the quality standards, enhance the corporate reputation and cares about the community and environmental welfares. Previous studies also confirmed that CSR practice is important as a sustainable strategy to growth and compete longer in the business (Desiyanti & Kassim, 2020;Ghadas et al, 2018;Samuel et al, 2011).…”
Section: Resultsmentioning
confidence: 62%
“…Previous studies had shown that managers' religiosity plays an important role as contributing factor towards SMEs' performance such as in Saudi Arabia (Alharbi et al, 2021) and Indonesia (Desiyanti & Kassim, 2020). Moreover, Ghadas et al (2018) revealed that it is crucial for managers to include the religiosity aspect in their business in terms of CSR so that it can give the highest benefit to the society and increase organizational performance and reputation. Tahir et al (2015) investigated the managers' perception towards religiosity and CSR in the Malaysian context.…”
Section: Managers' Religiositymentioning
confidence: 99%
“…24 Being a khalifah, Muslims must always concede that Allah is the only God that deserve to worship and that all possessions, wealth, expertise, abilities, positions and power belong to Allah as mentioned in Quran: "To Him belongs what is in the heavens and on earth, and all between them, and all beneath the soil." [Qur'an, Taha: 6] 25 Subsequently, Muslim's social responsibility is to manage these possessions to the best of their abilities with intention of creating benefit to the community. 26 They are not supposed to cause corruption in any form on earth (i.e.…”
Section: The Concept Of Corporate Social Responsibility From An Islam...mentioning
confidence: 99%
“…35 It is obvious that all responsibilities mentioned in the verse including helping relatives, orphans, poor, needy, wayfarers, and freeing of captives all are relevant to the CSR. 36 The term Maqasid is derived from a verb qaseda which means the goals and purposes. Maqasid itself means goals or objectives and when such term is attached to the word Syari'ah it specifically refers to goals or objectives of Syari'ah.…”
Section: Csr In the Context Of Maqasid Al-syari'ahmentioning
confidence: 99%